Prognosis of 'Lengthy' Febrile Convulsions - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
The outcome of children with status epilepticus (afebrile seizure >30 min) or lengthy febrile convulsions (>30 min) is reported by a British population based cohort study group that followed 16004 neonatal survivors born in one week in 1970 and assessed them after 5 and 10 years.